2006
DOI: 10.1002/jnr.20954
|View full text |Cite
|
Sign up to set email alerts
|

Temporal dynamics of neurite outgrowth promoted by basic fibroblast growth factor in chick ciliary ganglia

Abstract: Basic fibroblast growth factor (bFGF) is a potent and multifunctional neurotrophic factor that can influence neuronal survival and differentiation. It has been shown to modulate growth and orientation of neuritic processes both in intact organs and in neuronal cultures, with a wide spectrum of effects on different preparations. Here we report that it promotes neurite growth in developing parasympathetic neurons from the chick ciliary ganglion. We have used both organotypic cultures and dissociated neurons, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 53 publications
2
17
1
Order By: Relevance
“…The formation of neuronal processes has been reported to be influenced by several trophic factors, such as nerve growth factor (Lakshmi and Joshi, 2006;Liu et al, 2007), brainderived neurotrophic factor (BDNF) in the rat ganglion (Lin et al, 2006), insulin-like growth factor-I (Shiraishi et al, 2006), retinoic acid (So et al, 2006), basic fibroblast growth factor (Zamburlin et al, 2006), and vascular endothelial growth factor in cerebral cortical neurons (Jin et al, 2006). These processes can regenerate when damaged, and the direction in which these process regenerate may be affected by the local environmental factors (Szpara et al, 2007;Vogelezang et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The formation of neuronal processes has been reported to be influenced by several trophic factors, such as nerve growth factor (Lakshmi and Joshi, 2006;Liu et al, 2007), brainderived neurotrophic factor (BDNF) in the rat ganglion (Lin et al, 2006), insulin-like growth factor-I (Shiraishi et al, 2006), retinoic acid (So et al, 2006), basic fibroblast growth factor (Zamburlin et al, 2006), and vascular endothelial growth factor in cerebral cortical neurons (Jin et al, 2006). These processes can regenerate when damaged, and the direction in which these process regenerate may be affected by the local environmental factors (Szpara et al, 2007;Vogelezang et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In a well established model of peripheral neurons, cultured E7/E8 embryonic chick ciliary ganglion neurons, we have previously shown that FGF-2 can promote neuronal survival [4] and neurite outgrowth [25] in dissociated and organotypic cultures. Moreover, it induces long lasting changes in [Ca 2+ ] i through a mechanism mainly dependent on calcium influx from the extracellular medium [4].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it is known (supplementary material of Zamburlin et al, 2006;Arimura and Kaibuchi, 2007), that while new neurites can appear others can be retracted; therefore as a general model of neurite formation, we use a birth and death process (Goel and Rychter-Dyn, 1974) where birth corresponds to the formation of a neurite and death to its retraction. According to this process in the time interval ıt the probabilities of transition for birth and death are, respectively, k ıt = Prob(k → k + 1) and k ıt = Prob(k → k − 1); the master equation governing the process is then given, in differential form, by Goel and Rychter-Dyn (1974) …”
Section: Some Theoretical Considerationsmentioning
confidence: 99%
“…This function is of great relevance in the establishment of the correct connections between the individual components of the nervous system. Basic Fibroblast Growth Factor (bFGF) is one of the most extensively studied neurotrophic factors in this context (Abe and Saito, 2001), and it has been shown to exert different roles according to the specific experimental model: in many sensory and autonomic neurons it acts by promoting neurite growth (Perron and Bixby, 1999;Webber et al, 2005;Zamburlin et al, 2006), while in central neurons it has been shown to inhibit axonal growth (Catapano et al, 2004) or induce growth cone arrest and formation of branches and collaterals (Szebenyi et al, 2001). An equally relevant, although less studied, aspect is the role of the neurotrophic factor in the definition of the neuronal morphology, e.g.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation